2002
DOI: 10.1183/09031936.02.02322001
|View full text |Cite
|
Sign up to set email alerts
|

Allergens and endotoxin on mothers' mattresses and total immunoglobulin E in cord blood of neonates

Abstract: on behalf of the LISA study group Allergens and endotoxin on mothers9 mattresses and total immunoglobulin E in cord blood of neonates. J. Heinrich, G. Bolte, B.Hölscher, J. Douwes, I. Lehmann, B. Fahlbusch, W. Bischof, M. Weiss, M. Borte, H-E. Wichmann, on behalf of the LISA study group. #ERS Journals Ltd 2002. ABSTRACT: The current authors examined whether mite and cat allergen and bacterial endotoxin levels in dust of the mothers9 mattresses were associated with cord blood immunoglobulin (Ig)E (CB-IgE) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 32 publications
10
123
0
4
Order By: Relevance
“…Within the LISA cohort study there was an association between prenatal endotoxin exposure and IgE production [29]. Additional support for the important role which endotoxin exposure might play comes from a cross-sectional study, which found an association between exposure to higher levels of house-dust endotoxin with lower prevalence of allergic sensitisation in children [30].…”
mentioning
confidence: 70%
“…Within the LISA cohort study there was an association between prenatal endotoxin exposure and IgE production [29]. Additional support for the important role which endotoxin exposure might play comes from a cross-sectional study, which found an association between exposure to higher levels of house-dust endotoxin with lower prevalence of allergic sensitisation in children [30].…”
mentioning
confidence: 70%
“…The AIRALLERG study was conducted in the framework of four ongoing birth cohort studies of similar design: PIAMA in the Netherlands (Brunekreef et al, 2002), BAMSE in Sweden (Wickman et al, 2002) and GINI (von Berg et al, 2003) and LISA (Heinrich et al, 2002) in Germany. The AIRALLERG study was designed to obtain environmental samples, including dust samples from mattresses and living room floors, in the homes of 180 sensitized and 180 nonsensitized children in each country.…”
Section: Methodsmentioning
confidence: 99%
“…At the 2-or 4-, 6-, and 10-y follow-ups, the children were clinically examined by a pediatrician, and the parents completed several age-related questionnaires regarding their children's medical, nutritional, behavioral and socioeconomic characteristics. Details concerning the study background, representative recruitment strategy, inclusion and exclusion criteria and protocols have been extensively described elsewhere (Heinrich et al 2002;Zutavern et al 2006, von Berg et al 2013. Almost 50% of subjects were lost to follow-up during the first 10 y due to various circumstances, including withdrawals, the inability to trace the participants, and waning interest.…”
Section: Study Populationmentioning
confidence: 99%